2017
DOI: 10.1002/cb.1650
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of consumer willingness‐to‐pay for social responsibility in fruit and vegetable products: A cross‐country comparison using a choice experiment

Abstract: Choice experiments are used to assess consumer preferences and willingness‐to‐pay (WTP) for different food attributes worldwide. These studies also include credence attributes which are the product attributes that are not immediately observable to consumers without appropriate information and labelling, such as animal welfare, food safety, and social responsibility. Although choice experiment application has considered many of these attributes, studies focused on social responsibility are scant. Building on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Since the premium price expresses a payoff for the costs incurred by companies for implementing CSR (e.g. audit and reporting), several studies have attempted to reveal consumers' WTP (Aktar, ; De Pelsmacker, Driesen, & Rayp, ; Loureiro & Lotade, ; Miller et al, ). Most of these studies were carried out surveying consumers from both developed (Lombardi, Caracciolo, Cembalo, Lerro, & Lombardi, ; Viegas, Nunes, Madureira, Fontes, & Santos, ) and developing countries (Tait, Saunders, Guenther, & Rutherford, ; Wu, Yin, Xu, & Zhu, ), different food products (Hartmann et al, ; Mueller Loose & Remaud, ) and different CSR attributes (De Pelsmacker et al, 2005; Viegas et al, ; Del Giudice et al, ).…”
Section: Conceptual Background and Research Questionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the premium price expresses a payoff for the costs incurred by companies for implementing CSR (e.g. audit and reporting), several studies have attempted to reveal consumers' WTP (Aktar, ; De Pelsmacker, Driesen, & Rayp, ; Loureiro & Lotade, ; Miller et al, ). Most of these studies were carried out surveying consumers from both developed (Lombardi, Caracciolo, Cembalo, Lerro, & Lombardi, ; Viegas, Nunes, Madureira, Fontes, & Santos, ) and developing countries (Tait, Saunders, Guenther, & Rutherford, ; Wu, Yin, Xu, & Zhu, ), different food products (Hartmann et al, ; Mueller Loose & Remaud, ) and different CSR attributes (De Pelsmacker et al, 2005; Viegas et al, ; Del Giudice et al, ).…”
Section: Conceptual Background and Research Questionsmentioning
confidence: 99%
“…Most of these studies were carried out surveying consumers from both developed (Lombardi, Caracciolo, Cembalo, Lerro, & Lombardi, ; Viegas, Nunes, Madureira, Fontes, & Santos, ) and developing countries (Tait, Saunders, Guenther, & Rutherford, ; Wu, Yin, Xu, & Zhu, ), different food products (Hartmann et al, ; Mueller Loose & Remaud, ) and different CSR attributes (De Pelsmacker et al, 2005; Viegas et al, ; Del Giudice et al, ). However, the discrepancy encountered in previous studies in terms of premium prices detected, due to products, attributes and consumers investigated, do not allow us to extend the results observed (Miller et al, ). Moreover, given the lack of research focusing on Italian consumers, this study adds to the CSR literature examining consumers' WTP for food products meeting the expectations, in terms of CSR, of Italian consumers.…”
Section: Conceptual Background and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [4] conducted a choice experiment for coffee products and showed that the most important certification attribute is traceability, followed by organic, graded, environmentally friendly, and fair-trade certification. Miller et al [5] conducted a choice experiment for fruits and vegetables and investigated preferences for attributes such as health, environment, animal welfare/biodiversity, food safety, social responsibility, and quality. They showed that consumers prefer better standards of these attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies which utilized public perception focus on health (Harapan et al [36]), environment (Vollmer et al [37], Suparman, Folmer and Oud [38], Ghozali and Kaneko [39], Soo [40]), tourism (Anna [41]), transportation (Hendratmoko, Guritnaningsih, and Tjahjono [42], Ambarwati [43]), and trade (Kojima [44] and Miller et al [45]). Only two studies present public perception in the energy area in the Indonesian context, namely Lensink, Raster and Timmer [46] with observations about the WTP for solar lamps, and Kumashiro et al [47], which evaluated geothermal energy.…”
Section: User Perception To Evaluate Reliability Of Electricity Supplymentioning
confidence: 99%